Prolonged QT syndrome triggered by swimming: A mimicking cause of seizures not to be missed - Al Jarallah, Abdullah S. (Journal of Pediatric Neurology, 2005)
Epilepsy can sometimes be mimicked in children by uncommon conditions. We present a 6-year-old boy with congenital deafness and long QT syndrome (Jervell and Lange-Nielsen syndrome) triggered by swimming. He had bradycardia and a history of early seizures and deaths in the family. He had been misdiagnosed and treated as idiopathic generalized tonic-clonic epilepsy for three years without control.
Keywords: Prolonged QT syndrome; seizures; arrhythmia; deafness; swimming; electrocardiography